Runner's world complete book of running : everything you need to run for weight loss, fitness, and competition - Burfoot, Amby. ([Emmaus, Pa.] : Rodale ; [New York] : Distributed by Macmillan, 2009)
Explains key fitness and nutritional practices, providing coverage of everything from proper hydration and selecting appropriate footwear to improving endurance and marathon training.
pt. I. Beginning running -- 1. Get started on the right foot -- 2. Oprah did it, so can you -- 3. Buy the right shoes for you -- 4. Start right here -- pt. II. Running and nutrition -- 5. Eat the right foods at the right time -- 6. New nutrition truths for men -- 7. Try the vegetarian alternative -- 8. 15 superfoods for runners -- pt. III. Injury prevention -- 9. Prevent 5 common injuries -- 10. Train right to beat running injuries -- 11. Self-treatments that work -- 12. You can run, but you can't hide from the heat -- pt. IV. Women's running -- 13. Run smart and informed to save your life -- 14. 38 ways to improve your running -- 15. The answers you need to know -- pt. V. Building strength, endurance, and speed -- 16. 25 best training tips -- 17. The need for speed -- 18. The FIRST way to train -- 19. Beat 10 common running roadblocks -- pt. VI. The mental side of running -- 20. Train your brain for better performance -- 21. Yes, you can -- 22. 89 great motivational tricks -- 23. Reach all your goals -- pt. VII. Cross-training -- 24. Train better by running less -- 25. Treadmills to the rescue -- 26. Training the whole body -- 27. Get great abs now -- 28. Abs-olutely the best core exercises for runners -- pt. VIII. Weight loss for runners -- 29. Your personalized diet program -- 30. The ultimate runner's weight-loss plan -- 31. Eat smarter, lose weight, run stronger -- pt. IX. The half-marathon -- 32. Build both your speed and your endurance -- 33. Take the half-marathon challenge -- 34. Lessons learned for half-marathon wisdom -- pt. X. The marathon -- 35. 11 rules for marathon success -- 36. Incredible but true: Yasso 800s -- 37. The perfect marathon taper -- 38. The thinking runner's marathon plan -- 39. Will the marathon kill you?
Includes index.
Keywords: Running; Running -- Training